Retracted: Exploring the factors affecting disaster coordination between government agencies and NGOs in disaster relief distribution and rehabilitation activities: Evidence from Bangladesh. Issue 1 (3rd September 2020) - Uddin, Mohammed Mahin; Ali, Sumran; Khan, Tajdar; Reyad, Md. Amjad Hossain; Paul, Rajesh
Abstract : Retraction: Uddin, MM, Ali, S, Khan, T, Reyad, MAH, Paul, R. Exploring the factors affecting disaster coordination between government agencies and NGOs in disaster relief distribution and rehabilitation activities: Evidence from Bangladesh. J Public Affairs. 2020; e2373. https://doi.org/10.1002/pa.2373 . The above article, first published online on 03 September 2020 in Wiley Online Library (wileyonlinelibrary.com ), has been retracted by agreement between the authors, the journal's Editors‐in Chief, Professor Phil Harris and Professor Danny Moss, and John Wiley and Sons Ltd. The retraction has been agreed as there are fundamental corrections needed to improve the readability and accuracy of the article. The authors have been offered the opportunity to resubmit a revised version of the article to be peer reviewed and considered for publication.